2015
DOI: 10.1177/0149206315579511
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Store-Unit–Community Racial Diversity Congruence on Store-Unit Sales Performance

Abstract: We introduce the racial diversity congruence concept to examine how matching levels of racial diversity between store-unit employees and community members relate to store-unit sales performance. In a field study of 220 retail store units, we found evidence supporting social identity theory and information-based perspectives on the racial diversity congruence-sales performance relationship. Specifically, results show that a match between store-unit racial diversity and community racial diversity positively rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…A potential explanation is that firms in growth mode have cultures that are more receptive to unique, non-status quo ideas and are perhaps therefore more supportive of the views of and leadership of diverse others. Other work (e.g., Herring, 2009;Richard, Stewart, McKay, & Sackett, 2017) also supports the notion that sales performance may be an outcome variable that is particularly sensitive to gender and racial diversity effects. Specifically, they found that matching levels of diversity between store-unit employees and community members was positively related to store-unit performance.…”
Section: Discussion Of Meta-analysis Resultsmentioning
confidence: 75%
“…A potential explanation is that firms in growth mode have cultures that are more receptive to unique, non-status quo ideas and are perhaps therefore more supportive of the views of and leadership of diverse others. Other work (e.g., Herring, 2009;Richard, Stewart, McKay, & Sackett, 2017) also supports the notion that sales performance may be an outcome variable that is particularly sensitive to gender and racial diversity effects. Specifically, they found that matching levels of diversity between store-unit employees and community members was positively related to store-unit performance.…”
Section: Discussion Of Meta-analysis Resultsmentioning
confidence: 75%
“…The major difference between vertical faultlines and demographic faultlines is that while demographic faultlines typically focus on the overall subgrouping strength based on the demographic alignment on the same status, vertical faultlines capture the subgrouping phenomena across hierarchy-based (e.g., job ranks, status) subgroups. For the conceptualization of vertical faultlines, we also draw on the demographic representativeness approach (Avery et al, 2012; King et al, 2011; Richard et al, 2017), which argue that when demographic composition of managers (e.g., ethnicity) is misaligned with that of employees, a signal will be sent to employees that the organization does not value equal opportunity (Lindsey et al, 2017). Hence, vertical faultlines capture the multivariate demographic alignment (i.e., demographic match/mismatch) between two different job levels, which also differs from the demographic representativeness approach that only examines single-attribute compositional differences between managers and employees (i.e., management ethnic representativeness; Lindsey et al, 2017).…”
mentioning
confidence: 99%
“…To estimate the effect of RLMX, we used the polynomial regression technique and response surface methodology (Edwards, 1994; Shanock et al, 2010). In contrast to standard moderated regression analyses, polynomials allow us to assess the nonlinear and asymmetrical effects of a predictor such as RLMX (Richard et al, 2017). As the focus of our study is incongruence rather than congruence, namely whether the difference between LMX and unit-level LMX matters, we calculated the slopes of the surface with a3 = b1 − b2 and a4 = b3 − b4 + b5, where b1 is the beta for the individual LMX, b2 is the beta for the unit LMX, b3 is the beta for the individual LMX square, b4 is the beta for the cross-product of the individual LMX and unit-level LMX, and b5 is the beta for the unit-level LMX square.…”
Section: Methodsmentioning
confidence: 99%